Towards a methodological framework for vocal behavior analysis in popular singing (Per Musi, 2023)
We present in this article a methodological framework that combines tools capable of facilitating understanding of choices and interpretive intentions in Popular Singing, as well as perceiving semantic outcomes resulting from vocal procedures and their relationship with other elements of the song. The methodology covers physiological, acoustic, aesthetic, semiotic, and musical aspects. To achieve this, we use concepts and procedures from the semiotics of the song, the emotional qualities of the voice, understanding of musical moments and sound units. Finally, we apply the proposal, which will be experimented through the analysis of distinct interpretations of the same song, and we analyze the construction of the interpretive gesture and the meanings that emerge from the relationships that unfold in the song's plot.